The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/app.39583
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characteristics of swollen gellan gum hydrogels

Abstract: The behavior of swollen gellan gum hydrogels in terms of mechanical properties, weight loss, and cell growth inhibition of leachates is presented. Low-acyl gellan gum (LAGG), high-acyl gellan gum (HAGG), and a HAGG-LAGG blend were soaked in phosphate-buffered saline (PBS) at pH 7.4 and 37 C for up to 168 days. The gels exhibited their maximum mass loss and swelling after 28 days of immersion in PBS. LAGG gels exhibited lower value for mass loss and the chain-release diffusion coefficient than gels consisting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 35 publications
(49 reference statements)
3
17
0
1
Order By: Relevance
“…In this case, according to the authors, the side chains of the molecule are very important to the hydration rate and swelling of the compound. Hence, as reported in the work of Silva and coworkers (13), HA gellan has a greater capacity of swelling than LA. Thus, the branched chain present in HA gellan gum may have favoured its hydration and swelling, which could be also associated with the tendency of faster drug release, compared to LA gellan.…”
Section: Dissolutionsupporting
confidence: 53%
See 1 more Smart Citation
“…In this case, according to the authors, the side chains of the molecule are very important to the hydration rate and swelling of the compound. Hence, as reported in the work of Silva and coworkers (13), HA gellan has a greater capacity of swelling than LA. Thus, the branched chain present in HA gellan gum may have favoured its hydration and swelling, which could be also associated with the tendency of faster drug release, compared to LA gellan.…”
Section: Dissolutionsupporting
confidence: 53%
“…According to the literature, gellan gum molecules, when in solution, form double helix chains after heating and cooling, being stabilized by the presence of mono or divalent cations, thus forming aggregates that compose a three-dimensional network of crosslinked gel (12). According to Silva and coworkers (13), as HA gellan gum has a more branched chain, the steric hindrance of bulky groups within the double-helix implies a smaller proportion of molecules associated with this structure, compared to LA gellan gum. As drug release modulation by this polymer is related to the formation of these aggregates (14), the degree of interaction between the chains may have influenced drug release, which was reflected in the difference between polysaccharide formulation results.…”
Section: Dissolutionmentioning
confidence: 99%
“…In addition, GG formed a gel on contact with tear fluid 50 , which is advantageous for ophthalmic 50 drug delivery. GG hydrogels are therefore also stable during long-term culture in standard media and do not suffer from unwanted dissolution due to ionic exchange 51 . In addition to these gelation properties, GG's excellent optical clarity could prove advantageous in analysis of encapsulated cells 7 .…”
Section: Why Consider Gellan Gum?mentioning
confidence: 99%
“…The steady mass loss behavior of these gellan gum‐containing ICE gels can be explained by their chain release behavior. It has been proposed in our earlier studies that free gellan gum chains (those not associated with the gel network) are released first, while the network‐associated chains are released over a longer time frame. Therefore, it is suggested that when ICE gels are immersed in enzymes (lysozyme, trypsin), un‐associated GG and polyacrylamide chains are released during the rapid mass loss period (0–3 days), whereas the gel network‐associated chains are released during the remainder of the study (3–42 days).…”
Section: Resultsmentioning
confidence: 87%